Electrospun aluminum silicate nanofibers as novel support material for immobilization of alcohol dehydrogenase. (22nd October 2022) - Aziz, Iram; Sigurdardóttir, Sigyn Björk; Lehmann, Jonas; Nambi, Ashwin; Zhang, Wenjing; Pinelo, Manuel; Kaiser, Andreas
Abstract: Ceramic materials with high surface area, large and open porosity are considered excellent supports for enzyme immobilization owing to their stability and reusability. The present study reports the electrospinning of aluminum silicate nanofiber supports from sol-gel precursors, the impact of different fabrication parameters on the microstructure of the nanofibers and their performance in enzyme immobilization. A change in nanofiber diameter and pore size of the aluminum silicate nanofibers was observed upon varying specific processing parameters, such as the sol-composition (precursor and polymer concentration), the electrospinning parameters and the subsequent heat treatment (calcination temperature). The enzyme, alcohol dehydrogenase (ADH), was immobilized on the aluminum silicate nanofibers by physical adsorption and covalent bonding. Activity retention of 17% and 42% was obtained after 12 d of storage and repeated reaction cycles for physically adsorbed and covalently bonded ADH, respectively. Overall, the immobilization of ADH on aluminum silicate nanofibers resulted in high enzyme loading and activity retention. However, as compared to covalent immobilization, a marked decrease in the enzyme activity during storage for physically adsorbed enzymes was observed, which was ascribed to leakage of the enzymes from the nanofibers. Such fibers can improve enzyme stability and promote a higher residual activity of the immobilized enzyme as compared to the free enzyme. The results shown in this study thus suggest that aluminum silicate nanofibers, with their high surface area, are promising support materials for the immobilization of enzymes.